Effects of branched chain amino acids, l-citrulline, and alpha-glycerylphosphorylcholine supplementation on exercise performance in trained cyclists: a randomized crossover trial - Renee Nicole Harrington (Taylor & Francis Group, 2023)
Background Nutrition plays a key role in training and athletic performance and dietary supplements can make a small, but potentially valuable, contribution to achieving peak athletic performance. This study is the first to investigate the effects of supplementation from the combination of BCAAs, L-citrulline, and A-GPC on exercise performance. Methods In this randomized, double-blind, crossover study 30 male trained cyclists (age: 43.7 ± 8.5 years) completed a 20 km cycling time trial (TT) test and a high intensity endurance cycling (HIEC) test following a 7-day supplementation period with either a supplement containing 8 g BCAAs, 6 g L-citrulline, and 300 mg A-GPC or a placebo (15 g maltodextrin). For each trial, mean values for time to completion, peak and average power output, OMNI rating of perceived exertion, and visual analogue scale (VAS) responses on perceived exertion were computed for the 20 km TT test. Mean values for time to fatigue and VAS responses on perceived exertion were computed for the HIEC test. Procedures for dietary intake and exercise patterns were implemented to achieve consistency throughout the study period. Results There was a significant increase (p = .003) in peak power in the 20 km TT (354.27 ± 87.88 and 321.67 ± 63.65, for supplement and placebo trials, respectively) and a significant increase (p = .001) in time to fatigue in the HIEC test (0:19:49 ± 0:11:13 min and 0:14:33 ± 0:09:59 min, for supplement and placebo trials, respectively) with the test supplement compared to the placebo. With the test supplement, there was an average increase in TT peak power of 11% and an average increase in time to fatigue of 36.2% in the HIEC test compared to the placebo. There was no significant improvement in time to completion, average power, OMNI rating of perceived exertion, or VAS responses on perceived exertion in the TT test and no significant improvement in VAS measures of perceived exertion in the HIEC test. Conclusions The combination of BCAAs, L-citrulline, and A-GPC used in this study improves cycling performance and may be useful for individuals seeking to improve athletic performance, particularly in disciplines requiring lower body muscular strength and endurance.